DNA repair protein Rad18 restricts LINE-1 mobility. Issue 1 (December 2018) - Ariumi, Yasuo; Kawano, Koudai; Yasuda-Inoue, Mariko; Kuroki, Misao; Fukuda, Hiroyuki; Siddiqui, Rokeya; Turelli, Priscilla; Tateishi, Satoshi
Abstract Long interspersed element-1 (LINE-1, L1) is a mobile genetic element comprising about 17% of the human genome. L1 utilizes an endonuclease to insert L1 cDNA into the target genomic DNA, which induces double-strand DNA breaks in the human genome and activates the DNA damage signaling pathway, resulting in the recruitment of DNA-repair proteins. This may facilitate or protect L1 integration into the human genome. Therefore, the host DNA repair machinery has pivotal roles in L1 mobility. In this study, we have, for the first time, demonstrated that the DNA repair protein, Rad18, restricts L1 mobility. Notably, overexpression of Rad18 strongly suppressed L1 retrotransposition as well as L1-mediated Alu retrotransposition. In contrast, L1 retrotransposition was enhanced in Rad18-deficient or knockdown cells. Furthermore, the Rad6 (E2 ubiquitin-conjugated enzyme)-binding domain, but not the Polη-binding domain, was required for the inhibition of L1 retrotransposition, suggesting that the E3 ubiquitin ligase activity of Rad18 is important in regulating L1 mobility. Accordingly, wild-type, but not the mutant Rad18-lacking Rad6-binding domain, bound with L1 ORF1p and sequestered with L1 ORF1p into the Rad18-nuclear foci. Altogether, Rad18 restricts L1 and Alu retrotransposition as a guardian of the human genome against endogenous retroelements.